In‐vitro and in‐vivo evaluation of the modulatory effects of the multitarget compound ASS234 on the monoaminergic system. (30th January 2017) - Esteban, Gerard; Van Schoors, Jolien; Sun, Ping; Van Eeckhaut, Ann; Marco‐Contelles, José; Smolders, Ilse; Unzeta, Mercedes
Abstract: Objectives: To evaluate the in‐vitro and in‐vivo effects on monoaminergic neurotransmission of ASS234, a promising multitarget‐directed ligand (MTDL), for Alzheimer's disease (AD) therapy. Methods: In vitro was explored the effect of ASS234 on the monoaminergic metabolism in SH‐SY5Y and PC12 cell lines, and remaining activity of both monoamine oxidase (MAO) isoforms was assessed. The corresponding dopamine (DA), homovanillic acid (HVA) and 3, 4‐dihydroxyphenylacetic acid (DOPAC) and noradrenaline (NA) levels were determined by HPLC‐ED. In‐vivo experiments were carried out Wistar rats and intracerebral guide cannulas were implanted in the hippocampus and in the prefrontal cortex by sterotaxic coordinates. The day after microdialysis samples were collected and levels of 5‐HT, DA and NA were determined by (UHPLC) with electrochemical detector. Key findings: ASS234 induced a significant increase in serotonin (5‐HT) levels in SH‐SY5Y cells. In PC12 cells, ASS234 increased significantly the ratio of dopamine (DA)/(HVA + DOPAC), although no apparent differences in (NA) were observed. By in‐vivo microdialysis, ASS234 showed a significant increase in the extracellular levels of 5‐HT and NA in hippocampus whereas in the prefrontal cortex, DA and NA also increased significantly. Conclusions: This study reveals the ability of ASS234 a MTDL compound, to enhance the monoaminergic neurotransmission supporting its potential use in AD therapy.